????? ????? ???? ???????? ???????? ?????? "????? ?????? ??????? ?? ????? ???????" ??? ????? ??????? ????? ???????? ??? ?????? ???? ???? ??????? - Aida Maulidia Muzdalifatin; Muhammad Thohir; Muhammad Baihaqy (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2016)
Learning materials are all materials used to help teacher in their learning process in the classroom, and istima’ (listening skill) is one of the four language skills that are basis for mastering other language skills such as speaking, reading and writing. The book of Silsilah Al-Daurah Al-Mukathafah fi Al-Lughah Al-Arabiyah is a book whose teaching material is sourched from several books written by learning experts in the Middle East, such as ‘Arabiyah Bayna Yadayk and Durûs Al-Lughah Al-‘Arabiyah and others. Researchers want to know about how to fill and apply the material istima’ in the book Silsilah Al-Daurah Al-Mukathafah fi Al-Lughah Al-Arabiyah in order to provide the right solution to the problems in the book using Richards theory. This study uses qualitative descriptive method to analyze the content of the book and the application of istima’ material according to the book of Silsilah Al-Daurah Al-Mukathafah fi Al-Lughah Al-Arabiyah in the Al-Fathimiyah Islamic Boarding School in Tambakberas Jombang. This study also uses descriptive analysis methods in its applied research. According to Richards in the preparation of the material istima’ uses four approaches, Bottom-Up Processing, Top-Down Processing, Transactional and Interactional. The results of this study indicate that the istima’ material in the book Silsilah Al-Daurah Al-Mukathafah fi Al-Lughah Al-Arabiyah and the application using the Bottom-up Processing and Transactional, because the material and the application are more inclined giving a detailed meaning.